ENGLISH LANGUAGE LEARNING SOFTWARE - Shirshova, Irina; Sizova, Yuliya; Gabazov, Timur; Salynskaya, Tatiana (Revista Inclusiones, 2020)
The development of information and communication technologies and the status of English as the language of international communication, the professional mastery of which provides opportunities for effective activity and successful communication at the international level, have greatly influenced the use of innovative information technologies and the organization of the educational process of mastering English as a foreign language. With the use of software, students master all aspects of the language: phonetic, grammatical, lexical, and communicative, which allows them to more effectively and quickly learn the language material and acquire speech skills and abilities. The article presents an analysis of the research on various aspects of using software in learning English. According to an expert survey, positive aspects, principles, and opportunities of using software in learning English, as well as recommendations for their selection, are identified.